Adhesion in dentin prepared with Er,Cr:YSGG laser: Systematic review - Ana Catarina Silva; Paulo Melo; João Cardoso Ferreira; Teresa Oliveira; Norbert Gutknecht (Wolters Kluwer Medknow Publications, 2019)
Background: In dentistry, cavities prepared with Erbium lasers present more advantages, compared to traditional methods, but there is still a lack of investigation about the adhesion in dentin surfaces prepared with Erbium lasers, especially with Erbium, chromium:yttrium-scandium-gallium-garnet (Er,Cr:YSGG) laser. Aim: The purpose of this systematic review was to find out which might be "The most adequate adhesive and laser parameters for adhesion in dentin prepared with Er,Cr:YSGG laser." Methods: An electronic search was performed in the PubMed database. The search was limited to studies between 2009 and 2016. Results: Ten articles were selected to the systematic review according to TRANSPARENT REPORTING of Systematic Reviews and Meta-ANALYSES checklist. Conclusions: The adhesive that showed the best bond strength results in dentin prepared with Er,Cr:YSGG laser was the self-adhesive Clearfil™ SE (Kuraray), with preconditioning with 40% phosphoric acid. The settings 2 W, 75% water, 60% air, 140 μs pulse duration, and 20 Hz showed the best adhesion outcome.